ERCC1 is not expressed in hepatocellular cancer: A Turkish Oncology Group, Gastrointestinal Oncology Subgroup study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2010)
Purpose: Hepatocellular cancer (HCC) is a common malignancy with a high mortality rate. Existence of excisional repair cross complementation1 (ERCC1) is implicated in resistance to cisplatin treatment. Expression of ERCC1 in HCC is not known. In this study we aimed to find out whether a subset of HCC patients can be identified to benefit from cisplatin. Methods: Sixty-one patients with HCC who had enough tissue to do immunohistochemistry were identified in 3 institutions. Immunohistochemical staining was performed manually using the standard streptavidin-biotin-peroxidase method. Monoclonal anti-ER CC 1 (D-10) antibody from Santa Cruz Biotechnology (Santa Cruz, CA) was used. Results: Only one out of 61 patients (1.6%) had ERCC1 expression. Conclusion: Although around 10% of HCC patients respond to cisplatin, this is unlikely to be due to ERCC1 negativity. Pathways other than ERCC1 should be searched to find ways to help these patients' treatment strategies.
Keywords: ERCC1; hepatocellular cancer; immunohistochemistry; EXCISION-REPAIR GENES; LUNG-CANCER; CARCINOMA; CHEMOTHERAPY; CISPLATIN; RISK